Effects of self-efficacy enhancing program on foot self-care behaviour among elderly with diabetes in Rumah Seri Kenangan, Peninsular Malaysia - Ahmad Sharoni, Siti Khuzaimah (2017)
Background: Diabetes has a significant impact on health especially among the elderlypopulation. The Self-efficacy theory could improve foot self-care behaviour among the elderly with diabetes to prevent the risk of foot problems. There is a dearth of publications related to theory based intervention to improve foot self-care behaviour among the elderly with diabetes living in an institutional care in Malaysia. Objectives: This study aims to develop, implement and evaluate the effectiveness of a self-efficacy enhancing program on foot self-care behaviour among the elderly with diabetes in Rumah Seri Kenangan, Peninsular Malaysia.Methods: A Randomised Controlled Trial was conducted for 12 weeks in six Rumah Seri Kenangan, Peninsular Malaysia, Malaysia. Elderly with diabetes aged 60 years and above who fulfilled the inclusion criteria were invited to participate in this program. Using a randomised cluster design, the respondents were randomly allocated by an independent person into two groups (intervention and control). The intervention group received the self-efficacy enhancing program on foot self-care behaviour. Four self-efficacy components; performance accomplishments, vicarious experience, verbal persuasion, and physiological and emotional states were translated into program interventions. The program consisted of four visits; the first visit included screening and baseline assessment and the second visit involved 30 minutes of group seminar presentation. The third and fourth visits entailed a 20-minute one to one follow-up discussion and evaluation. A series of visits to the respondents was conducted throughout the program. Meanwhile, the control group received the usual health care. The primary outcome is foot-self-care behaviour. Foot care self-efficacy (efficacy expectation), foot care outcome expectation, knowledge of foot care, quality of life, fasting blood sugar and foot condition are the secondary measures. Data were analysed with descriptive and inferential statistics (t-test, Mann-U, Chi-Square, Fisher’s exact, repeated measures Analysis of Variance, Mixed Designs Analysis of Variance and McNemar) using the Statistical Package for the Social Sciences version 20.0. Results: 184 respondents were recruited but only 76 met the selection criteria and were included in the analysis at baseline, week-4 and week-12 post-intervention. The acceptability profile rate and healthcare provider compliance were high. Foot self-care behaviour, foot care self-efficacy (efficacy expectation), foot care outcome expectation and knowledge of foot care improved in the intervention group compared to the control group (p<0.05). However, some of these improvements did not significantly differ compared to the control group for QoL physical symptoms, QoL psychosocial functioning, common skin conditions, overall foot hygiene and overall foot condition (p>0.05). Fasting blood sugar, other foot conditions and infections, nail conditions and foot complications did not show any statistical improvement across the time effects between the two groups (p>0.05). Conclusion: The self-efficacy enhancing program improved foot self-care behaviour with respect to the delivered program thus reducing the risk of foot problems. It is expected that in the future, the Self-efficacy theory can be incorporated into diabetes education to enhance foot self-care behaviour and improve physical and psychosocial outcome of elderly with diabetes living in other institutional care facilities.